...

SuperProdigy

From: US
Posts: 6
Votes: 18
_ _ _ _ _ _ _ (A + C + D) (A + C + D) (A + B + D) = A D + A D + B D plz proofthat 1) Proof that:

 

Answer No.1

Anonymous

From: -
Posts: -
Votes: -
We have to Prove :- (A + C + D) (A + C ' + D )(A ' + B ' + D ') = A D ' + A ' D + B ' D (A + C + D) (A + C ' + D ) (A ' + B ' + D ') = (AA + A C ' + AD + AC + CC ' + CD + AD + C ' D + DD ) ( A' + B' +D') = ( A + A C ' + AD + 0 + CD + C'D + D) ( A ' + B ' + D ') = ( A( 1 + C ' ) + AD + D ( C + C ' ) + D ) ( ( A ' + B ' + D') = (A + AD + D)( A ' + B ' + D ') = AB' + A D' + ADB ' + A ' D + B ' D = A B ' + AD ' + A' D + B ' D AB' is not effecting this term so we have. = A D ' + A ' D + B ' D

Your Comment/Solution

Post As: Anonymous [Change]
Enter